The clinical characteristics of Chinese elderly patients with different durations of type 2 diabetes mellitus - Yu, Yun; Xie, Kaipeng; Lou, Qinglin; Xia, Hui; Wu, Dan; Dai, Lingli; Hu, Cuining; Shan, Shan; Wang, Kunlin; Tang, Wei (Frontiers in Endocrinology, 2022)
Aims: To explore the clinical characteristics among elderly (aged ≥60 years) patients with type 2 diabetes (T2DM) of different durations. Methods: Clinical characteristics were investigated in 3840 elderly T2DM patients according to their different durations of diabetes (< 1 year, 1~5 years, 5~10 years, and ≥ 10 years). Results: There were 972, 896, 875 and 1097 patients with a duration of diabetes of <1, 1~5, 5~10 and >10 years, respectively. In logistic regression models adjusted for age, sex, education and BMI, elderly T2DM patients with a duration of diabetes of ≥ 10 years were more likely to reach the comprehensive control targets for TC (ORTC = 1.37, 95% CI =1.15-1.64), LDL-C (ORLDL-C = 1.39, 95% CI =1.16-1.66) and TG (ORTG = 1.75, 95% CI =1.45-2.12). Elderly T2DM patients with a duration of diabetes of 1~5 years were more likely to achieve the HbA1c control target (ORHbA1c = 1.92, 95% CI = 1.59-2.31) than elderly T2DM patients with a duration of diabetes of <1 year. Furthermore, in elderly T2DM patients with a duration of diabetes of 5~10 years or ≥ 10 years, the duration of diabetes was independently associated with diabetic macrovascular complications (coronary heart disease and peripheral artery disease). In elderly T2DM patients with a duration of diabetes of over 10 years, the duration of diabetes was independently associated with diabetic nephropathy after adjusting for age, sex, education and smoking status. Conclusions: It is worth noting that the clinical characteristics of elderly patients with type 2 diabetes in different stages of diabetes are different. Keywords: clinical characteristics, elderly patients, type 2 diabetes mellitus, duration of diabetes, stages of diabetes